LANDING SITE PREDILEKSI LALAT SUMBA (Hippobosca sp.) PADA SAPI BALI - Julianty Almet; Lidya Emmanuela Ngefak; Aji Winarso (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The development of cattle farming in East Nusa Tenggara is one of the potential contributors to support local demands. In order to achive this goal, cattle have to be free from the disease and parasites. One of the most common ecto- parasites that also serve as disease vector is bitting flies. Hippobosca sp. is bitting flies that commonly breed in the semi-arid tropics area with low rate of rainfall and high temperature such as East Nusa Tenggara Province. The aims of this research are to observe and determine the landing site of Hippobosca sp. in certain area of the cattle and to identify the predilection of Hippobosca sp. in Bali cattle. This research conducted in two different Bali cattle farms, Agricultural High School of Kupang in Kupang District and Neotnana Farmers Group in Kupang City. The observation was conducted to measure flies landing activity on five cows of each farm. The activity of the flies were observed in 5 major body regio, head area, neck area, thoraco-abdominal area, extremity area and perineal area. Landing flies was collected every 2 hours from 06:00 till 18:00 local time, and pooled based on body area they collected from. This procedure repeated 8 times in 4 weeks in each farm. The result showed that neck area is as the major landing site predilection of Hippobosca sp. in Bali Cattle. Neck area showed the highest density of landing flies, with total 3313 flies observed, followed by thoraco-abdominal, perineal, extremity and head area, with total amount of 2811, 1689, 1037, and 172 flies, respectively.